Relative Influence of Plastic Debris Size and Shape, Chemical Composition and Phytoplankton-Bacteria Interactions in Driving Seawater Plastisphere Abundance, Diversity and Activity - Cheng, Jingguang; Jacquin, Justine; Conan, Pascal; Pujo-Pay, Mireille; Barbe, Valérie; George, Matthieu; Fabre, Pascale; Bruzaud, Stéphane; Ter Halle, Alexandra; Meistertzheim, Anne-Leila; Ghiglione, Jean-François (Frontiers in Microbiology, 2021)
The thin film of life that inhabits all plastics in the oceans, so-called “plastisphere”, has multiple effects on the fate and impacts of plastic in the marine environment. Here, we aimed to evaluate the relative influence of the plastic size, shape, chemical composition and environmental changes such as a phytoplankton bloom in shaping the plastisphere abundance, diversity and activity. Polyethylene (PE) and polylactide acid (PLA) together with glass controls in the forms of meso-debris (18 mm diameter) and large-microplastics (LMP; 3 mm diameter), as well as small-microplastics (SMP) of 100 m diameter with spherical or irregular shapes were immerged in seawater during 2 months. Results of bacterial abundance (confocal microscopy) and diversity (16S rRNA Illumina sequencing) indicated that the three classical biofilm colonization phases (primo-colonization after 3 days; growing phase after 10 days; maturation phase after 30 days) were not influenced by the size and the shape of the materials, even when a diatom bloom (Pseudo-nitzschia sp.) occurred after the first month of incubation. However, plastic size and shape had an effect on bacterial activity (3H leucine incorporation). Bacterial communities associated with the material of 100 µm size fraction showed the highest activity compared to all other material sizes. A mature biofilm developed within 30 days on all material types, with higher bacterial abundance on the plastics compared to glass, and distinct bacterial assemblages were detected on each material type. The diatom bloom event had a great impact on the plastisphere of all materials, resulting in a drastic change in diversity and activity. Our results showed that the plastic size and shape had relatively low influence on the plastisphere abundance, diversity and activity, as compared to the plastic composition or the presence of a phytoplankton bloom.